VD_FINDINFO Jug / 2025 / 301 vom 6. Mai 2025 - VD Tribunal cantonal (2025)
VIOL, CONTRAINTE SEXUELLE, TORT MORAL | 123 ch. 1 al. 1 CP, 126 al. 1 CP, 126 al. 2 let. b CP, 144 al. 1 CP, 177 al. 1 CP, 180 al. 1 CP, 180 al. 2 let. a CP, 181 CP, 189 al. 1 CP, 190 al. 1 CP, 217 al. 1 CP